Cùng trừ mỗi tỉ số trên đi 1 đơn vị ta được:
$\frac{2a+b+c+d}{a}$ -1=$\frac{a+2b+c+d}{b}$ -1=$\frac{a+b+2c+d}{c}$ -1=$\frac{a+b+c+2d}{d}$ -1
=> $\frac{a+b+c+d}{a}$=$\frac{a+b+c+d}{b}$ =$\frac{a+b+c+d}{c}$=$\frac{a+b+c+d}{d}$
Từ đây ta suy ra 2 trường hợp:
+ Trường hợp 1:
Nếu a + b + c + d $\neq$ 0 => a = b = c = d
=> M = 1 + 1 + 1 + 1 = 1 . 4 = 4
+ Trường hợp 2:
Nếu a + b + c + d = 0 thì
a + b = - ( c + d ) ; b + c = - ( d + a )
c + d = - ( a + b ) ; d + a = - ( b + c )
Do đó: M = ( -1 ) + ( - 1 ) + ( - 1 ) + ( - 1) = -4